Privacy and data protection in the time of pandemic - Zulhuda, Sonny (2020)
How does the Pandemic bring about the challenges to privacy and data protection? Is there anything we should be worried about? The isolation, restricted movement, disease control measures, tracking apps, contact tracing, work-from-home, online learning… and the list goes on. All these dots when connecting to each other will reveal that privacy concern is real and its protection can be a critical game-changer. Just in time to test the efficiency of the Personal Data Protection law. This is the gist of my keynote presented at the Sixth International Conference on Internet Applications, Protocols and Services (NETAPPS2020). This International Conference is held by the Computing School of the Universiti Utara Malaysia (UUM).